2016
DOI: 10.14367/kjhep.2016.33.5.23
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the sensory, cognitive and physical functions of young-old and old-old individuals

Abstract: Objectives: This study aims to define the relationships between the sensory, cognitive and physical functions of young-old and old-old individuals. Methods: Participants were 10,451 elderly individuals aged 65 and above, raw data of a 2014 National Survey on Korean Older Persons was used. To investigate the relationships among the sensory, cognitive, and physical functions, a structural equation model was used. Results: The key analysis results are summarized as follows; 5% had poor vision function(young-old 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…An increase in the population of older adults implies an increase in the population wherein individuals' sensory, cognitive, and physical functions decrease [8,9]. Previous studies have shown that physical functioning tends to decrease with age [8,9]. In the NSOP 2014, 43.7% of the survey respondents aged 65 years or above believed that their health was poor [7].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the population of older adults implies an increase in the population wherein individuals' sensory, cognitive, and physical functions decrease [8,9]. Previous studies have shown that physical functioning tends to decrease with age [8,9]. In the NSOP 2014, 43.7% of the survey respondents aged 65 years or above believed that their health was poor [7].…”
Section: Introductionmentioning
confidence: 99%